A Microbial Survey of Second Hand Clothe Samples Collected from Baghdad Market - Al-Easawi, Nada Abdulrahman F; Emran, Faiza Kadhim (Al-Nahrain Journal of Science, 2017)
Abstract:Second hand represent one of the sources of illness due to environmentally related disease and injury. Used clothes are sold all over the country since they are very cheap compared with the new ones. The current study included collecting samples from different used clothing markets in Baghdad and comparing the efficiency of detergents used to reduce microbial load in the garments. The samples were adult's clothes, babies' clothes, and fabric toys. Isolation and identification of bacteria with CFU were done to determine which cloth samples carry the highest bacterial contamination and dominant pathogenic microbes associated with skin infection. Culture and biochemical methods were used for the identification. Samples were washed using two types of detergents (soap, granulated detergent) to investigate the efficiency of these detergents in reducing bacterial contamination in such clothes. The results showed that the dominant isolate bacteria in adult clothes were Staphylococcus sp. and Enterobacteriace sp. while Enterobacteriace sp., Bacillus sp. in baby clothes and Bacillus sp. in fabric toys. The results of CFU found to be the highest in baby's clothes (4x106), fabric toys (2.2x104 ), adult clothes (20x102 )respectively. Results showed that the isolated fungi were Aspergilus flavus, Aspergilus niger, Rhizopus. After washing with detergents including soap and granulated detergent, the results showed that the granulated detergent is more effective in reducing bacterial and fungal contamination than soap in all samples. This study concluded that babies' cloths are vulnmrable to contaminating with bacteria and fungi then fabric toys followed by adult clothes. It's recommended to wash second hand clothes using other methods to remove both bacterial and fungal contamination such as disinfectants then ironing.